Pre-clinical evaluation of targeting autophagy for the treatment of Oral Squamous Cell Carcinoma - Magnano, Stefania (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2021)
Oral Squamous Cell Carcinoma (OSCC) is the sixth most common form of cancer worldwide. It is typically aggressive and closely correlated with disease recurrence and poor survival. Chemoresistance is a critical problem associated with OSCC leading to therapeutic failure, tumour recurrence and progression. Autophagy, a physiological catabolic process that allows the degradation and recycling of unnecessary or dysfunctional cellular components, has acquired an emerging interest in cancer as it has been shown to be frequently activated in tumour cells treated with chemotherapeutics. Whether drug-induced autophagy represents a mechanism that allows cancer cells to survive or a pro-death mechanism associated with apoptosis remains controversial. Additionally, a role for autophagy during cancer development has also been proposed, but its role in OSCC remains poorly understood. The aim of this study was to determine whether autophagy is involved in the cellular response to cisplatin in OSCC and in the development of chemoresistance and whether targeting autophagy represents a valuable treatment strategy to sensitise cells to chemotherapy. Moreover, this preclinical study investigated the expression of key autophagic regulatory proteins in oral cancer patient samples in order to elucidate the role of autophagy in OSCC development. Cisplatin, a representative OSCC chemotherapeutic agent, was shown to concurrently induce both apoptosis and autophagy in two OSCC cell lines, SCC4 and SCC9. To evaluate the role of cisplatin-induced autophagy in OSCC and to investigate the relationship between autophagy and apoptosis, the effect of targeting autophagy on cisplatin-induced apoptosis was examined. Autophagy inhibition using two early stage autophagy inhibitors, 3-methyladenine and SAR405, did not sensitise OSCC cells to cisplatin treatment. This finding was supported by data showing that knockdown of the key autophagy protein ATG5, necessary during the early stage of the autophagic process, did not significantly modulate sensitivity to cisplatin. In contrast, treatment of cells with two late stage autophagy inhibitors, chloroquine and bafilomycin-A1, was shown to significantly enhance cisplatin-induced apoptosis in OSCC cells. However, off-target, autophagic-independent effects of these inhibitors could not be ruled out. Interestingly, inhibition of cisplatin-induced apoptosis with the general caspase inhibitor Z-VAD-fmk abrogated cisplatin-induced autophagy in OSCC cells further indicating a complex interplay between autophagy and apoptosis. The crosstalk between cisplatin-induced autophagy and apoptosis was further investigated by examining the signalling pathway(s) involved in the cellular response to cisplatin. Cisplatin was shown to induce oxidative stress by increasing the generation of Reactive Oxygen Species (ROS). Moreover, pre-treatment of cells with the antioxidant N-acetyl cysteine was shown to protect cells from cisplatin-induced apoptosis and autophagy and to suppress cisplatin-induced JNK activation. Additionally, the JNK inhibitor SP600125 was shown to partially reduce both autophagy and caspase 3 activation, suggesting a coordinated activation of cisplatin-induced autophagy and apoptosis in OSCC through the ROS/JNK signalling pathway. Analysis of chemoresistance in OSCC was carried out through the generation of a cisplatin-resistant OSSC cell line (SCC4cisR) obtained by pulsed stepwise exposure of SCC4 cells to cisplatin. The SCC4cisR cell line was shown to be approximately 14 times more resistant to cisplatin than the parental SCC4 cell line and displayed a reduced apoptotic ability following cisplatin treatment. Autophagy did not appear to play a role in acquired resistance to cisplatin in this cell model. In contrast, cellular adaptation to ROS-induced oxidative stress was identified as a mechanism implicated in cisplatin resistance. In fact, enhanced ROS generation and concurrent activation of the antioxidant Nrf2/HO-1 pathway were demonstrated in the SCC4cisR cells. Furthermore, targeting the antioxidant systems glutathione and Nrf2 with inhibitors was shown to partially restore the cisplatin-sensitive phenotype in the SCC4cisR cells, indicating that this may prove a valuable strategy to improve chemotherapy in OSCC patients. Finally, evaluation of the expression of key autophagic proteins LC3, p62 and Beclin-1 in OSCC tissue samples from two independent patient cohorts (Spanish and Irish) was performed by western blotting and immunohistochemistry, respectively. An increase in the expression of LC3 and Beclin-1 along with a decrease in p62 in cancerous samples compared to non-cancerous samples was demonstrated, suggesting autophagy activation during OSCC progression. Moreover, preliminary results showed a potential application of LC3 and Beclin-1 as biomarkers for OSCC detection, thus further analysis with a bigger sample size may be warranted.
APPROVED
Keywords: Oral Cancer; Autophagy; Apoptosis; Oxidative Stress; Chemoresistance; Cisplatin